Coverage Prediction for Triple Diffraction Scenarios - Mehmet B. Tabakcioglu , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Electromagnetic waves emanating from the transmitter can reach to the receiver by reflection, direct or diffraction mechanism. In urban areas, dominant mechanism is diffraction. Thanks to using of high frequency, the obstructions can be modeled as a knife-edge. Coverage prediction is vital to install reliable and high-quality communication systems. In this study, a triple diffraction coefficient is derived for Uniform Theory of Diffraction (UTD) model and used for coverage problem. Coverage problems could be solved by the developed program in MATLAB computationally. Simulation results obtained in developed program are compared with FEKO electromagnetic wave propagation simulation software.